Can domestic production of iLUC-free feedstock from arable land supply Sweden's future demand for biofuels?. Issue 6 (2nd November 2017) - Prade, Thomas; Björnsson, Lovisa; Lantz, Mikael; Ahlgren, Serina
ABSTRACT: The increasing biofuel production from agricultural crops has been suggested to cause indirect land use change (iLUC). This increases interest in biofuel feedstocks that qualify as iLUC-free: (1) residues without a market, (2) crops from previously unused arable land, (3) additional crops and (4) biomass from intensified production. In the present study, biofuel potential from such feedstocks was quantified for Sweden and compared against the predicted biofuel demand from agricultural resources in 2030. The results indicate that straw (category 1) could cover up to 37% of future biofuel demand. Grass leys from intensified production (category 4), set-aside and abandoned land (category 2) and excess grass silage (category 1) could cover up to 79%. Intermediate and ecological focus area crops (category 3) could contribute up to 21%. To realize the biofuel targets, a high implementation rate of additional iLUC-free feedstock is needed. Future studies need to investigate impacts of low-iLUC policies.